Literasi Linguistik dalam Pendidikan Inklusif untuk Pengembangan Kemampuan Berbahasa pada Anak Berkebutuhan Khusus - Abd. Rahman; Hasan Basri; Helman Al-Qudish; Mas'odi Mas'odi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
Inclusive education plays an important role in ensuring that all children, including those with special needs, have equal opportunities to develop, especially in terms of language skills. This article describes the application of language skills in inclusive education as an approach to support the development of language skills in children with special needs (ABK). This study uses a literature approach by reviewing various literature on language skills, inclusive education, and language skills development in ABK. The results of the study indicate that language skills strategies such as multisensory methods, teaching aids, and adaptive techniques have proven effective in improving verbal and nonverbal communication skills in ABK, as well as improving their understanding of social situations. The conclusion of this study highlights the importance of collaboration between educators, parents, and policy makers in implementing language skills optimally in an inclusive environment to support the overall development of ABK.